2020
DOI: 10.1016/j.jcis.2019.11.102
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution of supported lipid bilayers intercalated with quantum dots

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Nonlipid surfactant vesicles have also been used to trap NPs, , as they can offer enhanced durability over conventional lipids. Vesicles loaded with NPs or quantum dots can then be fused onto supportive substrates to form planar supported lipid bilayers (SLBs) doped with hydrophobic inclusions. , These methods allow membrane properties such as lipid orientation and membrane fluidity to be probed using microscopic and spectroscopic techniques, and the use of closed vesicles can mimic physical aspects of the cellular environment such as membrane curvature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonlipid surfactant vesicles have also been used to trap NPs, , as they can offer enhanced durability over conventional lipids. Vesicles loaded with NPs or quantum dots can then be fused onto supportive substrates to form planar supported lipid bilayers (SLBs) doped with hydrophobic inclusions. , These methods allow membrane properties such as lipid orientation and membrane fluidity to be probed using microscopic and spectroscopic techniques, and the use of closed vesicles can mimic physical aspects of the cellular environment such as membrane curvature.…”
Section: Introductionmentioning
confidence: 99%
“…However, the strain induced by high curvature of spherical vesicles complicates NP loading, and conventional vesicle assembly offers poor control of embedded NP concentrations, sometimes resulting in Janus-like or bare vesicles. , This can also cause inconsistent NP loading in SLBs, which complicates the study of doped-membrane properties. Further, the supportive substrates of SLBs can artificially influence lipid phase transitions and interfere with trapped NP distribution by encouraging aggregation or pushing NPs into the exterior lipid leaflet. , These issues consequently obscure electrophysiology measurements of doped membranes, which are influenced by the amounts and relative locations of trapped NPs and can further reveal potential collective effects of embedded NPs and transmembrane potentials. Such electric fields play vital regulatory roles in cellular behaviors: For example, transmembrane electrical potentials affect cell proliferation, neuronal migration, and the uptake of antibiotic peptides. While embedded hydrophobic NPs can lower membrane capacitance, , the coupled electrical and structural properties of doped lipid membranes (e.g., the relationship between membrane capacitance and thickness) under applied transmembrane potentials remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it is widely believed that cell membranes contain functional domains ranging from tens of nanometers to several hundred nanometers. ,, These domains apparently participate in many important cellular processes, such as protein organization, lipid regulation, endocytosis, signal transduction, and so forth. Multicomponent model lipid membranes are also known to exhibit phase-separated domains depending on the lipid composition and temperature . However, recent studies by our group using super-resolution stimulated emission depletion (STED) nanoscopy revealed the presence of much smaller nanoscale dynamical domains in phase-separated uncharged biological membranes which are closely connected to preferential binding of NPs and pore-forming toxins. In this context, several studies on model membranes have also revealed the potential of X-ray reflectivity (XR) to probe the molecular structure of the membranes. For single-component bilayers, information regarding the change in head, tail, and the bilayer thinning can be obtained. Also, for multicomponent systems, existence of phases with different heights can be revealed by the XR technique. , This, in principle, could also enable detection of phase-specific binding of NPs on the membranes.…”
Section: Introductionmentioning
confidence: 99%